A Review of Literature on Lean Manufacturing Tools and Implementation Based on Case Studies - Prawira, Yoga; Ishak, Aulia; Anizar, Anizar (Jurnal Sistem Teknik Industri, 2024)
This research focuses on reviewing the Lean Manufacturing (LM) implementation which is widely applied in the manufacture company to overcome or reduce waste. The aim of this article is to find out more about the influence on the industry sector. This research was developed by collecting research from indexed databanks of Scopus, Science direct, ResearchGate, etc. This review study is significant to identify the application of lean manufacturing in dealing with waste through implementation into several case studies. A total of 24 articles were selected, taking into account criteria such as keywords, article titles and publications of international publishers, which were selected through a systematic process. This study found that the application of lean manufacturing is a method that brings many advantages that work by minimizing losses and waste, and the Value Stream Mapping method is more often used as part of several Lean Manufacturing techniques to identify and analyze the occurrence of waste while providing solutions that lead to improvement. process and cost reduction.